Rachel West and the fallen starlet - Mills, Emma, 1989- (Berkley Mystery, 2026)
"Baby doll top, gladiator sandals, and fully loaded iPod at the ready--it's 2008 in Los Angeles, and Rachel West is a little less starry-eyed than your average ingenue. There's never been a better time to be an entertainment journalist, but the road to writing glossy profiles starts with copyediting a celeb gossip rag. Hey, it pays her bills. Most of them, at least. Everything changes when Rachel befriends Molly Byrne--former child star and current tabloid fave due to her drunken escapades and rotating cast of boyfriends--in a nightclub bathroom. When Molly is found dead, all of Hollywood accepts her death as an overdose. But Rachel knows for a fact her friend was clean, so when Molly's favorite paparazzo, Casper, tells her he thinks Molly was murdered, she believes him. With the help of a ragtag group of residents from her apartment building, a handsome detective, and her trusty flip phone, Rachel must solve the mystery of Molly's death before she's written off for good"-- Provided by publisher.